Chemical defensive symbioses in the marine environment. (30th August 2013) - Lopanik, Nicole B.; Clay, Keith
Summary Marine organisms are a prolific source of natural products, many of which have become the target of pharmacological investigations. As well as being bioactive, these compounds can play an important role in the survival of the organisms and potentially affect community structure. Sessile invertebrates such as sponges, cnidarians, bryozoans and tunicates, in particular, are an especially rich source of ecologically relevant compounds. These organisms are typically soft‐bodied and unable to escape predators, and as such, they rely on chemical defence for their persistence. These invertebrates are also frequently hosts for microbial symbionts. Marine microbes are a prolific source of bioactive natural products, many of which can be allelopathic and prevent the growth of pathogens. For sessile marine invertebrates, which often have both bioactive natural products and microbial symbionts, it is logical to hypothesize that microbial symbionts may produce the secondary metabolites. While symbionts are often thought to be responsible for producing bioactive natural products that play a role in host defence, relatively few studies have experimentally demonstrated that symbiont‐produced compounds defend the hosts. One reason for this is the difficulty of manipulating the host–symbiont relationship, which is often obligate for one or both partners. Given the importance of natural products to marine invertebrates for defence, the prevalence of symbiosis in the marine environment and the diverse metabolic capabilities of micro‐organisms, symbiont‐mediated host chemical defence may be more prevalent than currently understood. In this review, I document evidence supporting chemical defensive symbioses in marine organisms, discuss commonalities and differences among the diverse relationships, and provide future research directions. Epibiont‐produced defensive compounds would seem to result in the most efficient manner of protection, as the compounds are most accessible to the predators. By contrast, endosymbiont‐produced compounds may need to be transported to exposed tissues. Elucidating mechanisms to transport symbiont‐produced defensive compounds within the host will provide greater insight into the breadth and complexity of host–symbiont interactions. Another important unexplored issue is how the hosts are able to tolerate symbiont‐produced metabolites that are often eucaryotic cell effectors. A greater understanding of defensive symbiosis will result from detailed studies of the co‐evolution of predator, host and symbiont, and if or how predators can influence the production of defensive metabolites.